Ibadah dan Kepuasan Hidup pada Muslim yang Berhijrah: Kelekatan kepada Tuhan sebagai Mediator - Siregar, Juliarni; Ateerah Abdul Razak; Kurniawan, Yohan; Nursalihah Ahmad Raston; Nindy Amita; Ateerah binti Abdul Razak; Kurniawan, Nur Saliha Binti Ahmad Raston (Psikis : Jurnal Psikologi Islami, 2024)
When Muslims perform hijrah, they have transformed their lives, including their worship, from a life of wrongdoing to the path of righteousness (repentance/taubat). While research on Muslim samples has consistently demonstrated that worship increases life satisfaction significantly, few researches have been able to elucidate how worship can generate life satisfaction in Muslims. This research aimed to find out whether attachment to God is significant in mediating the influence of worship on life satisfaction. This research used quantitative research to collect 205 samples of Muslims who performed hijrah in Pekanbaru through snowball sampling. The statistical analysis using the structural equation model with partial least squares (SEM-PLS), revealed that attachment to God significantly mediates the impact of worship on life satisfaction (β = 0.07, T = 2.49, p-values = 0.01). The upsilon (v) value indicated that the mediating effect of attachment to God was still relatively modest. The results of this research contributed to the advancement of Islamic psychotherapy grounded in worship practices to strengthen the connection with God and feel more satisfied with life